Monitoramento físico-químico do processo de malteação de cevada utilizada para a produção de cerveja tipo pilsen - Santos, Luciana Machado de Oliveira dos (2013)
Barley is the fourth most harvested cereal in the world, and the existing varieties only with the characteristics of the type for the production of beer are grown mainly in the south of Brazil. Malt is a product obtained by the malting or partial germination of cereal grains. The present work aims to obtain the data quality control through analytical techniques (DTA - Differential Thermal Analysis, TG - Thermogravimetry, DSC - Differential Scanning Calorimetry, Microscopy and Enzyme Activity), of the malting process to produce malt type Lagers. Barley seeds (Hordeum vulgare sp.) moistened in a glass container were used, through the process interspersed involving wetting with distilled water and moments dried in an oven at a controlled temperature of 18°C was then placed to germinate in a perforated form at the top of greenhouse with water in the tray at the bottom of the equipment, required to maintain the moisture with layer thickness of 2 cm at 20°C for 72h. The samples were removed after 10h in immersion, 36h and 72h germination. Analyses were made of malting barley samples and also malt in nature, and standard malt. The malt produced had a moisture content of 5,98%. TG curves shows a first water loss (dehydration) followed stability and to a second and third consecutive losses related to oxidative burning of the organic material. DTA curves obtained simultaneously shows a first endothermic peak (dehydration) followed by stability and a third and second exothermic peaks related to oxidative burning of the organic material. The Microscopy showed granules of barley in natura and experimental malt with sizes of 20μm, from rounded to oval shapes, and only rounded shapes and rough surface respectively. There was an increase in the enzymatic activity of the enzyme α-amylase malt trial for barley, and it was not possible to obtain enzymatic index equal to or higher than the standard malt, this difference relates to the malting method adopted for this experiment. Although the malting present great variation of time and temperature for each step, it is possible to produce quality lager malt obeying the moisture content during the process, and achieving a increased enzymatic activity of α-amylase. Brewers industries can analyze your own malt quickly and efficiently through the analysis and thermoanalytical microscopy in order to ensure greater standardization of the final product and check how his main raw material, may behave along the brewing process.